The environmental impact of health care for musculoskeletal conditions: A scoping review. - Bayden J McKenzie; Romi Haas; Giovanni E Ferreira; Chris G Maher; Rachelle Buchbinder (PLoS ONE)
Background Health care has significant environmental impact. We performed a scoping review to map what is known about the environmental impact of health care for musculoskeletal conditions. Methods We included published papers of any design that measured or discussed environmental impact of health care or health support services for any musculoskeletal condition in terms of climate change or global warming (e.g., greenhouse gas emissions it produces). We searched MEDLINE and Embase from inception to 2 May 2022 using keywords for environmental health and musculoskeletal conditions, and performed keyword searches using Google and Google Scholar. Two independent reviewers screened studies. One author independently charted data, verified by a second author. A narrative synthesis was performed. Results Of 12,302 publications screened and 73 identified from other searches, 122 full-text articles were assessed for eligibility, and 49 were included (published 1994 to 2022). Of 24 original research studies, 11 measured environmental impact relating to climate change in orthopaedics (n = 10), and medical aids for the knee (n = 1), one measured energy expenditure of laminar versus turbulent airflow ventilation systems in operating rooms during simulated hip replacements and 12 measured waste associated with orthopaedic surgery but did not relate waste to greenhouse gas emissions or environmental effects. Twenty-one editorials described a need to reduce environmental impact of orthopaedic surgery (n = 9), physiotherapy (n = 9), podiatry (n = 2) or occupational therapy (n = 1). Four narrative reviews discussed sustainability relating to hand surgery (n = 2), orthopaedic surgery (n = 1) and orthopaedic implants (n = 1). Conclusion Despite an established link between health care and greenhouse gas emissions we found limited empirical data estimating the impact of musculoskeletal health care on the environment. These data are needed to determine whether actions to lower the carbon footprint of musculoskeletal health care should be a priority and to identify those aspects of care that should be prioritised.